Women vs feminism : why we all need liberating from the gender wars - Williams, Joanna (Emerald Publishing, 2017)
Statistics tell us there has never been a better time to be a woman but feminists are quick to point out that women are still victims of everyday sexism. This title explores what life is like for women today. It's time to ditch a feminism that appears remote from the concerns of most women and, worse, pitches men and women against each other.
Keywords: Women.; Feminism.; elektronické knihy; electronic books